Pengaruh Kegiatan Menggunting Kertas Terhadap Motorik Halus Anak Kelompok A Di TK GKPI Tarutung Kota - Krisna Paradayani Yonata Banurea; Emmi Silvia Herlina; Hisardo Sitorus (LPPM Politeknik Pratama, 2023)
One of the activities that can enhance a child's fine motor skills is the activity of cutting. The purpose of cutting activities is to train eye-hand coordination, hand muscles, and concentration. Cutting can serve as the initial preparation stage for a child's writing, especially when holding a pencil. Cutting activities are one of the stimuli that educators can use to develop a child's fine motor skills, especially fine motor skills. Children will be able to coordinate their visual perception and hand activities through cutting activities. The aim of this research is to determine the significant impact of cutting paper activities on the fine motor skills of Group A in GKPI Tarutung City Kindergarten. The research method used in this study is a quantitative descriptive research method. The population consists of all children in Group A at GKPI Tarutung City Kindergarten, totaling 20 children. The improvement in fine motor skills can be seen from the accuracy of the children's indicator variables X and Y. The influence of cutting paper activities on the fine motor skills of Group A children at GKPI Tarutung Kindergarten resulted in an R-squared value of 0.365. From the determination coefficient (r^2), it can be understood that cutting paper activities account for 36.5% of the fine motor skills of Group A children at GKPI Tarutung City Kindergarten. Thus, the alternative hypothesis (Ha) indicating a significant impact of cutting paper activities on the fine motor skills of Group A at GKPI Tarutung City Kindergarten is accepted, while the null hypothesis (H0) is rejected.